Regular Breakfast Consumption and its Predictors Based on the Social Cognitive Theory in Female Students of Hamadan University of Medical Sciences - Nooshin Salimi; Akram Karimi-Shahanjarini*; Ghodratollah Roshanaei (Hamadan University of Medical Sciences, 2014)
Background and Objectives: Despite associating regular breakfast consumption habits with a range of health benefits, the rate of skipping the meal is high. The present study was conducted to determine the factors associated with breakfast consumption among female students of Hamadan University of Medical Sciences based on the Social Cognitive Theory (SCT). Materials and Methods: The present cross-sectional study was carried out on 423 female students in different faculties of Hamadan University of Medical Sciences. Participants were selected through multistage random sampling. The frequency of breakfast consumption and SCT variables, including knowledge, hope, outcome expectancies, observational learning, social support and self-efficacy, was measured using a self-administered questionnaire. Data were analyzed in SPSS-16 using the chi-square test, the correlation test and the linear regression analysis. Results: 24% of the students stated that they always ate breakfast. 10% of the students skipped breakfast. On average, the students ate breakfast 4.2 times a week. Self-efficacy (p<0.001) and social support (p<0.001) were good predictors of breakfast consumption in the students. These two variables were able to predict 64% of the variance in breakfast habits. Conclusion: The results show that self-efficacy and social support should be targeted in the design of interventions intending to increase breakfast consumption among female university students.